Epoxy resins, curing agents, compounds, and modifiers : an industrial guide - Flick, Ernest W. (Noyes Publications, 1993)
The second edition of this industrial guide describes over 2800 epoxy resins, curing agents, compounds, and modifiers. Information is based on material supplied by 71 manufacturers or distributors of these products. Each raw material or product is described, as available, with typical assay or checkpoint figures and a brief summary of important features or applications. Additional sections are the Suppliers Addresses and a Trade Name Index.